Pengaruh Motivasi Kerja, Iklim Organisasi Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan (Studi Empiris Pada PT. Pos Indonesia Persero Cabang Kantor Pos SPP Erlangga Semarang). - Rama Pramudya Putra Hadi Santoso; Askar Yunianto (SEIKO : Journal of Management & Business, 2022)
Abstract This study aims to test and analyze the influence of work motivation, organizational climate and work stress on job satisfaction. The object of research in writing this thesis is PT. POS Indonesia Persero Branch of SPP Erlangga Semarang POST Office. The sampling technique in this study was to use the Random Sampling technique with a total of 100 respondents. The analytical tool used in this study is multiple regression analysis, where previously validity and reliability tests were carried out. The results of the research are: (1) Job motivation has a positive effect on job satisfaction, the higher the job motivation, the more job satisfaction will increase. (2) The organizational climate has a positive effect on job satisfaction, the better the organizational climate, the better the job satisfaction. (3) Work stress negatively affects work stress, the lower the work stress, the more job satisfaction will increase. Keywords : Work Motivation, Organizational Climate, Work Stress, and Job Satisfaction